A calixpyrrole derivative acts as an antagonist to GPER, a G-protein coupled receptor: mechanisms and models - Rosamaria Lappano; Camillo Rosano; Assunta Pisano; Maria Francesca Santolla; Ernestina Marianna De Francesco; Paola De Marco; Vincenza Dolce; Marco Ponassi; Lamberto Felli; Grazia Cafeo; Franz Heinrich Kohnke; Sergio Abonante; et al. (The Company of Biologists, 2015)
Estrogens regulate numerous pathophysiological processes, mainly by binding to and activating estrogen receptor (ER)α and ERβ. Increasing amounts of evidence have recently demonstrated that G-protein coupled receptor 30 (GPR30; also known as GPER) is also involved in diverse biological responses to estrogens both in normal and cancer cells. The classical ER and GPER share several features, including the ability to bind to identical compounds; nevertheless, some ligands exhibit opposed activity through these receptors. It is worth noting that, owing to the availability of selective agonists and antagonists of GPER for research, certain differential roles elicited by GPER compared with ER have been identified. Here, we provide evidence on the molecular mechanisms through which a calixpyrrole derivative acts as a GPER antagonist in different model systems, such as breast tumor cells and cancer-associated fibroblasts (CAFs) obtained from breast cancer patients. Our data might open new perspectives toward the development of a further class of selective GPER ligands in order to better dissect the role exerted by this receptor in different pathophysiological conditions. Moreover, calixpyrrole derivatives could be considered in future anticancer strategies targeting GPER in cancer cells.